Rab11-FIP1 phosphorylation by MARK2 regulates polarity in MDCK cells. Issue 1 (2nd January 2017) - McRae, Rebecca; Lapierre, Lynne A.; Manning, Elizabeth H.; Goldenring, James R.
ABSTRACT: MARK2/Par1b/EMK1, a serine/threonine kinase, is required for correct apical/basolateral membrane polarization in epithelial cells. However, the specific substrates mediating MARK2 action are less well understood. We have now found that MARK2 phosphorylates Rab11-FIP1B/C at serine 234 in a consensus site similar to that previously identified in Rab11-FIP2. In MDCK cells undergoing repolarization after a calcium switch, antibodies specific for pS234-Rab11-FIP1 or pS227-Rab11-FIP2 demonstrate that the spatial and temporal activation of Rab11-FIP1 phosphorylation is distinct from that for Rab11-FIP2. Phosphorylation of Rab11-FIP1 persists through calcium switch and remains high after polarity has been reestablished whereas FIP2 phosphorylation is highest early in reestablishment of polarity but significantly reduced once polarity has been re-established. MARK2 colocalized with FIP1B/C/D and p(S234)-FIP1 in vivo . Overexpression of GFP-Rab11-FIP1C wildtype or non-phosphorylatable GFP-Rab11-FIP1C(S234A) induced two significant phenotypes following calcium switch. Overexpression of FIP1C wildtype and FIP1C(S234A) caused a psuedo-stratification of cells in early time points following calcium switch. At later time points most prominently observed in cells expressing FIP1C(S234A) a significant lateral lumen phenotype was observed, where F-actin-rich lateral lumens appeared demarcated by a ring of ZO1 and also containing ezrin, syntaxin 3 and podocalyxin. In contrast, p120 and E-Cadherin were excluded from the new apical surface at the lateral lumens and now localized to the new lateral surface oriented toward the media. GFP-FIP1C(S234A) localized to membranes deep to the lateral lumens, and immunostaining demonstrated the reorientation of the centrosome and the Golgi apparatus toward the lateral lumen. These results suggest that both Rab11-FIP1B/C and Rab11-FIP2 serve as critical substrates mediating aspects of MARK2 regulation of epithelial polarity.